PENGUATAN KAPASITAS PERSIAPAN PEMBERDAYAAN KOMUNITAS ADAT TERPENCIL (KAT) MELALUI BIMBINGAN TEKNIS PENGURUS YAYASAN PAPUA PENUH DAMAI (PAPEDA) - Wahyudin, Urip; Lefaan, Avelinus; Manggaprouw, Jecqueline F. (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2025)
The Papua Penuh Damai Foundation (PAPEDA) is a social service institution that focuses on community empowerment activities and plays a vital role in the strategy of reaching indigenous communities. The community service activities aim to improve the competence of PAPEDA Foundation administrators in providing services to the Yaur Tribe through empowerment activities for Remote Indigenous Communities (KAT) in Nabire Regency, Central Papua Province. The methods used in this activity include interactive lectures, group discussions, and hands-on practice. This activity is carried out systematically through a flow of activities including preparation, implementation, and closing. The results of the activity show an increase in knowledge and skills in understanding the flow of empowerment planning activities through the preparation stages, namely social mapping, initial assessment, feasibility studies, workshops, planning programs, and community empowerment. Thus, the technical guidance activity is a tactical step in strengthening the institutional role of the foundation and addressing the challenges of KAT empowerment.